Mood and Voice in Alain Robbe-Grillet’s novels - Zumalde Arregi, Imanol (Tropelías: Review of Literary Theory and Comparative Literature, 1995)
This article has a propose: to throw some light on that confusing field of semiotics known as narratology with the help of the normative contribution of Gérard Genette and François Jost. Nevertheless, the article makes use of Alain Robbe-Grillet’s Iiterary work to, somehow, base and support in literary practise, what Genette and Jost have proposed. In the end, after establishing the theoretic fundations of analysis, the subsidiary, that is, the study of the narratological configuration of Robbe-Grillet’s novels, comes to form the leading threat of the exposition.